The city as an inhospitable space: territory of the invasion theatre (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This text discusses the city as an inhospitable and violent space, and how a theater of invasion may relate to this urban space, positing itself as a dissident strategy in relation to the street’s functionalism and as a resistance to the culture of violence. This material also discusses the idea of ​​conflict as a context for the processes of artistic creation and ocupation of the urban space realized by theatrical experiences.
Keywords: Street theater; Violence; Spatialaties